To the New World and Back Again: Return Migrants in the Age of Mass Migration. (March 2019) - Abramitzky, Ran; Boustan, Leah; Eriksson, Katherine
The authors compile large data sets from Norwegian and US historical censuses to study return migration during the Age of Mass Migration (1850–1913). Norwegian immigrants who returned to Norway held lower-paid occupations than did Norwegian immigrants who stayed in the United States, both before and after their first transatlantic migration, suggesting they were negatively selected from the migrant pool. Upon returning to Norway, return migrants held higher-paid occupations relative to Norwegians who never moved, despite hailing from poorer backgrounds. These patterns suggest that despite being negatively selected, return migrants had been able to accumulate savings and could improve their economic circumstances once they returned home.